Islamic populism in Indonesia and the Middle East - Hadiz, Vedi R. 1964- (Cambridge, United Kingdom Cambridge University Press, 2017)
"In a novel approach to the field of Islamic politics, this provocative new study compares the evolution of Islamic populism in Indonesia, the country with the largest Muslim population in the world, to the Middle East. Utilising approaches from historical sociology and political economy, Vedi R. Hadiz argues that competing strands of Islamic politics can be understood as the product of contemporary struggles over power, material resources and the result of conflict across a variety of social and historical contexts. Drawing from detailed case studies across the Middle East and Southeast Asia, the book engages with broader theoretical questions about political change in the context of socio-economic transformations and presents an innovative, comparative framework to shed new light on the diverse trajectories of Islamic politics in the modern world"-- Provided by publisher.
1. Introduction -- 2. Islamic politics and the emergence of a new Islamic populism -- 3. The genesis of Islamic populism: historical legacies -- 4. Modernisation and the Cold War: paving the way -- 5. Pathways of political failure: dissent from the fringe -- 6. A study in political marginality: the Indonesian Darul Islam Movement and its heirs -- 7. Navigating through democracy: a pathway to power? -- 8. Navigating through neoliberalism: a pathway to power? -- 9. Conclusion.
Includes bibliographical references (pages 190-214) and index.
Keywords: Islam and politics -- Indonesia; Islam and politics -- Middle East; Populism -- Indonesia; Populism -- Middle East; Indonesia -- Politics and government; Middle East -- Politics and government